Specialist Savvy Versus Generalist Grit: Elucidating the Trade‐Offs in Adaptive Dietary Ecomorphology Amongst African Green and Bush Snakes - Hanlie M. Engelbrecht; Kimberley E. J. Chapelle; Graham J. Alexander (Ecology and Evolution)
ABSTRACT Kinetic feeding bones of macrostomatan Afrophidian snakes enable them to consume diverse prey types. While significant research has focused on functional feeding morphology in snakes, it often emphasizes broad taxonomic comparisons or species with distinct dietary ecologies. There is limited knowledge of how small variations in prey type composition may influence feeding morphology among closely related species sharing similar ecological niches. African Green and Bush Snakes (Philothamnus) feed primarily on frogs (anurophagous) and lizards (saurophagous), but the degree of intraspecific dietary generalization and specialization remains unclear. Thus, our study had three objectives: (1) to evaluate proportional differences in anurophagy and saurophagy between Philothamnus species, (2) quantitatively assess the shape differences in four of the main cranial bones functional in feeding, and (3) explore models of diet evolution. We hypothesized that differences in feeding morphology would reflect the extent of dietary specialization and/or generalization. Macroevolution diet analysis results indicated two main diet groups: anurophagous specialists and anuro‐saurophagous generalists. We included 14 species to reconstruct ancestral dietary states within a phylogenetic framework and analysed five representative species using geometric morphometric methods to assess skull shape variation related to dietary specialization and generalization. Geometric morphometric shape analyses show that the jawbones of anurophagous specialists (P. angolensis and P. hoplogaster) have higher mechanical advantage (MA), pronounced posteriorly curved maxillary teeth, deeper mandibular fossae on a more convex shaped compound, wider proximal quadrates, and deeper quadromandibular joint articulations. Conversely, anuro‐saurophagous generalists (P. occidentalis, P. natalensis and P. semivariegatus) have longer and thinner jaw bones with lower MA, a more horizontal dorsal quadrate, and high shape variation in maxillae and pterygoids. These findings suggest that dietary morphology is malleable and pervasive even among congeners with fine‐scaled differences in prey type proportions. Dietary specialization and generalizations among the African Green and Bush Snakes appear to exist along a continuum. Dietary ecomorphology appears to be influenced by phylogenetic relationships and may have evolved in dual mode, i.e., gradual specialization and punctuated shifts in dietary generalisation in response to ecological opportunity.